IMPROVING PERSONAL RESILIENCE AND STUDENT LEARNING ACHIEVEMENT THROUGH PROBLEM-BASED INSTRUCTION LEARNING - Joko Purwanto; Gunawan Gunawan; Jaka Wijaya Kusuma (Yayasan Education and Social Center, 2023)
Using the problem-based instruction learning model, this study aims to increase personal resilience and student achievement. The subjects of this study were 32 class VII students of SMP Negeri 1 Banyumas. This type of research is a class action consisting of three cycles. At the end of each cycle, an assessment is made regarding teacher activity, student activity, student personal resilience, and learning achievement—data collection techniques comprised of teacher and student activity observation sheets, individual resilience questionnaires, and tests. The results showed that using problem-based instruction, personal resilience, and student learning achievement were proven to increase. This can be seen from the quantitative data for each cycle